Strategi Fundrising Filantropi Islam Dalam Meningkatkan Kesejahteraan Masyarakat (Studi Kasus Koin Berkah Di Desa Gunungteguh) - Hafidz, Abdul (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
Islamic philanthropy is one source of progress for Muslims. However, the Islamic philanthropy movement will not be able to run well if it is not supported by an adequate fundraising strategy so that the fundraising process runs smoothly. The Blessed Coin Institute in Gunungteguh Village is a philanthropic institution that tries to collect coin funds to be distributed for social benefit. Every individual keeps a tin of blessed coins in his house, then he can put coins into the tin at any time and in any amount. The proceeds from collecting blessing coins are used for social benefit. Therefore, this research focuses on two things; 1) What is the role of blessed coins in improving the welfare of the people of Gunungteguh Village? 2) What is the fundraising strategy for Blessing Coins in optimizing the Islamic Philanthropic Movement in Gunungteguh Village?To obtain maximum results, this research uses field research with a descriptive qualitative approach using the Miles and Huberman model. Data analysis techniques use data reduction, data presentation, and conclusion drawing/verification. To test the validity of the data, this was done by extending observations, increasing persistence, and triangulation.The results of this research are first, the Blessing Coin Institution has a quite significant role in improving the welfare of the Gunungteguh Village community. This role can be categorized into three things, namely; as a facilitator, donor and leader. These three roles are not only able to improve community welfare, but are also able to increase public awareness of philanthropy. Second, the Blessing Coin Institute uses four types of fundraising strategies, namely; face to face, direct mail, special events, and competitors. Apart from that, the Blessing Coin Institute also uses two fundraising strategies, namely; direct fundraising and indirect fundraising.Keywords: Fundraising Strategy, Islamic Philanthropy, Blessing Coins